Membentuk Karakter Peserta Didik Melalui Pembelajaran Matematika Realistik di MI/SD - Lara Vardia Putri; Hidayanti Azkia; Isknadar Salamin; Djuita Hidayati (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Mathematics is part of the curriculum in Indonesia and has a very important role at every level of education. So that mathematics learning is expected to produce an important contribution in shaping students' character. Mathematics learning should be well designed by inserting character values in learning planning so that the goal of building student character can be achieved. The author will examine one example of realistic mathematics learning. The aim of realistic mathematics learning is to ensure that students not only achieve success in the cognitive aspect, but also experience positive changes in their attitudes and character.